A new disease of maize in Bahia, Brazil, with special reference to its casual organism - Ram, Asha; Ram, Chhatthoo; Rocha, Herminio Mahia (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
In the State of Bahia, Brazil, a new disease was observed in maize. The difficulty in classifying the causative organism is described in this paper.